High-Risk Intracranial Atherosclerotic Stenosis Despite Aggressive Medical Treatment: Protocol for a Prospective Nested Case-Control Study - Wang, Tao; Luo, Jichang; Liu, Changyi; Yang, Bin; Xu, Ran; Li, Long; Yang, Kun; Zhang, Chao; Wang, Yabing; Chen, Yanfei; Gao, Peng; Chen, Jian; et al. (Frontiers in Neurology, 2022)
Introduction Intracranial atherosclerotic disease (ICAD) is one of the most important etiologies of ischemic stroke, especially in Asia. Although medical treatment was recommended as the first-line therapy for ICAD, the recurrent stroke rate was still high in severe stenosis of ICAD despite aggressive medical treatment. Traditionally, the degree of luminal stenosis is used as the principal index for stroke risk stratification in ICAD patients, while recent evidence suggested that symptomatic atherosclerotic plaques were characterized by plaque features and hemodynamics. This prospective, longitudinal, nested case-control study aims to identify multimodal imaging predictors of high-risk ICAD patients refractory to medical treatment and explore a refined risk stratification model based on the above multimodal imaging predictors. Methods This prospective, longitudinal, nested case-control study will include 400 symptomatic ICAD patients with 50% to 99% of stenosis treated with aggressive medical therapy. All patients who meet eligibility criteria will be assessed by multimodal imaging examination from three aspects including lumen stenosis, plaque characteristics, and hemodynamic features. The enrolled patients will receive aggressive medical management including antiplatelet therapy and cardiovascular risk control. The primary outcome is the ischemic stroke or death attributable to the lesion of the target vessel within 1 year. The secondary endpoints are (1) any stroke or death; (2) all-cause mortality; (3) any stroke out of the territory of responsible lesion; (4) functional outcome, modified Rankin scale (mRS). Ethics and dissemination This study has been approved by the ethics committee of our center ([2021]083) and prospectively registered (Registration No: ChiCTR2100048832). Study findings will be disseminated through peer-reviewed publications and presentations at scientific meetings.